APOE/TOMM40 genetic loci, white matter hyperintensities, and cerebral microbleeds. Issue 8 (26th August 2015) - Lyall, Donald M.; Muñoz Maniega, Susana; Harris, Sarah E.; Bastin, Mark E.; Murray, Catherine; Lutz, Michael W.; Saunders, Ann M.; Roses, Allen D.; Valdés Hernández, Maria del C.; Royle, Natalie A.; Starr, John M.; Porteous, David J.; et al.
Abstract : Background: Two markers of cerebral small vessel disease are white matter hyperintensities and cerebral microbleeds, which commonly occur in people with Alzheimer's disease. Aim and/or hypothesis: To test for independent associations between two Alzheimer's disease‐susceptibility gene loci – APOE ε and the TOMM 40 '523' poly‐T repeat – and white matter hyperintensities/cerebral microbleed burden in community‐dwelling older adults. Methods: Participants in the Lothian Birth Cohort 1936 underwent genotyping for APOE ε and TOMM 40 523, and detailed structural brain magnetic resonance imaging at a mean age of 72·70 years (standard deviation = 0·7; range = 71–74). Results: No significant effects of APOE ε or TOMM 40 523 genotypes on white matter hyperintensities or cerebral microbleed burden were found amongst 624 participants. Conclusions: Lack of association between two Alzheimer's disease susceptibility gene loci and markers of cerebral small vessel disease may reflect the relative health of this population compared with those in other studies in the literature.